Effect of WhatsApp-based education on the knowledge and attitudes of integrated health service post cadres toward anemia prevention in children under five - Gayuh Siska Laksananno; Trimar Handayani; Sadar Prihandana (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Anemia in children under five remains a major public health problem in Indonesia because it can affect growth, cognitive development, and immune function. Integrated health service post cadres play an important role in community-based anemia prevention programs. However, limited knowledge and attitudes among cadres may reduce the effectiveness of health promotion activities. Digital health education through WhatsApp has become a practical and accessible educational medium for improving cadre capacity. Purpose: To assess changes in integrated health service post cadres’ knowledge and attitudes regarding anemia prevention in children under five after receiving WhatsApp-based education. Method: This study used a pre-experimental design with a one-group pretest-posttest approach. The study was conducted from April to June 2026 involving 40 Integrated health service post cadres from eight public health centers in Tegal City. Data were collected using knowledge and attitude questionnaires before and after the educational intervention delivered through WhatsApp. Data analysis was performed using the Wilcoxon Signed Rank Test. Results: Before the intervention, most respondents had poor knowledge (47.5%) and moderate attitudes (40%) regarding anemia prevention in children under five. After the intervention, the proportion of respondents with good knowledge increased to 65%, while positive attitudes increased to 55%. The Wilcoxon Signed Rank Test showed a significant improvement in knowledge (Z = -5.214; p < 0.001) and attitudes (Z = -4.112; p < 0.001) after the WhatsApp-based education intervention. Conclusion: WhatsApp-based education was effective in improving the knowledge and attitudes of Integrated health service post cadres regarding anemia prevention among children under five in Tegal City. WhatsApp can be used as an alternative digital health education medium because it is flexible, accessible, and supports continuous learning among community health cadres.